Question
upstudy study bank question image url

Express \( \frac{x^{2}+6 x-4}{(x+2)^{2}(x-4)} \) in partial fractions. Hence, or otherwise, obtain the first three non-zero terms in the Maclaurin expansion of \( \frac{x^{2}+6 x-4}{(x+2)^{2}(x-4)} \)

Ask by Rowe George. in the United Kingdom
Feb 04,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The partial fraction decomposition of \( \frac{x^{2} + 6x - 4}{(x + 2)^{2}(x - 4)} \) is: \[ \frac{2}{(x + 2)^2} + \frac{1}{x - 4} \] The first three non-zero terms of its Maclaurin series expansion are: \[ \frac{1}{4} - \frac{9}{16}x + \frac{23}{64}x^2 \]

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Reviewed and approved by the UpStudy tutoring team

The Deep Dive

To express \( \frac{x^{2}+6 x-4}{(x+2)^{2}(x-4)} \) in partial fractions, we start by assuming the form: \[ \frac{x^{2}+6 x-4}{(x+2)^{2}(x-4)} = \frac{A}{x+2} + \frac{B}{(x+2)^{2}} + \frac{C}{x-4} \] Multiplying through by the denominator \( (x+2)^{2}(x-4) \), we have: \[ x^{2}+6x-4 = A(x+2)(x-4) + B(x-4) + C(x+2)^{2} \] Expanding the right-hand side: 1. \(A(x+2)(x-4) = A(x^2 - 4x + 2x - 8) = A(x^2 - 2x - 8)\) 2. \(B(x-4) = Bx - 4B\) 3. \((x+2)^{2} = x^{2} + 4x + 4\), thus \(C(x+2)^{2} = C(x^2 + 4x + 4)\) Combining: \[ Cx^2 + (A - 2A + B + 4C)x + (-8A - 4B + 4C) \] Setting coefficients equal to those on the left-hand side provides a system of equations: 1. \(A + C = 1\) (coefficient of \(x^2\)) 2. \(-2A + B + 4C = 6\) (coefficient of \(x\)) 3. \(-8A - 4B + 4C = -4\) (constant term) Solving these equations: From (1): \(C = 1 - A\). Substituting into (2): \[ -2A + B + 4(1 - A) = 6 \implies -6A + B + 4 = 6 \implies B = 6A + 2 \] Now, substituting \(B\) and \(C\) in equation (3): \[ -8A - 4(6A + 2) + 4(1 - A) = -4 \\ -8A - 24A - 8 + 4 - 4A = -4 \\ -36A - 4 = -4 \\ -36A = 0 \implies A = 0 \] From \(A = 0\): - \(C = 1\) - \(B = 2\) Thus, the partial fraction decomposition is: \[ \frac{0}{x+2} + \frac{2}{(x+2)^{2}} + \frac{1}{x-4} = \frac{2}{(x+2)^{2}} + \frac{1}{x-4} \] Next step, we obtain the first three non-zero terms in the Maclaurin expansion: The function breaks down as: 1. For \( \frac{2}{(x+2)^{2}} \): \[ \frac{2}{(2 + x)^{2}} = \frac{2}{4} \cdot (1 - \frac{x}{2})^{-2} \approx \frac{1}{2} \left( 1 + 2\frac{x}{2} + 3\left(\frac{x}{2}\right)^{2} + \cdots \right) = \frac{1}{2} \left( 1 + x + \frac{3x^2}{4} + \cdots \right) \] Results in \( \frac{1}{2} + \frac{x}{2} + \frac{3x^{2}}{8} + \cdots \) 2. For \( \frac{1}{x-4} \): \[ \frac{1}{-4(1 - \frac{x}{4})} \approx -\frac{1}{4}(1 + \frac{x}{4} + \cdots) = -\frac{1}{4} - \frac{x}{16} + \cdots \] Combining these expansions gives us: \[ \frac{1}{2} - \frac{1}{4} + \left( \frac{x}{2} - \frac{x}{16} \right) + \left( \frac{3x^{2}}{

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy